2012
DOI: 10.5923/j.economics.20120207.05
|View full text |Cite
|
Sign up to set email alerts
|

External Debt Relief and Economic Growth in Nigeria

Abstract: This study examined the structural break relationship between external debt and economic gro wth fro m 1980 to 2009 with a view to examine the effect of external debt relief on economic growth in Nigeria. The effect o f huge external debt of less developed countries is believed to impede investment resources. This has resulted in debt restructuring of various kinds in Nigeria with some concessional loans, as well as the external debt relief in 2005. A decade after the debt relief critical sectors of the econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…In addition, Emmanuel (2012) assess the impact of public debt on economic growth in Nigeria, where he found a negative and quite significant impact of public debt on economic growth in the long-run, and a positive effect in the short-run. Furthermore, Ekperiware & Oladeji (2012) examine the effect of external debt relief on economic growth in Nigeria between 1975 and 2005. They found a structural break in the relationship between economic growth and external debt, where the external debt relief made more resources available for economic growth.…”
Section: Empirical Literaturementioning
confidence: 99%
“…In addition, Emmanuel (2012) assess the impact of public debt on economic growth in Nigeria, where he found a negative and quite significant impact of public debt on economic growth in the long-run, and a positive effect in the short-run. Furthermore, Ekperiware & Oladeji (2012) examine the effect of external debt relief on economic growth in Nigeria between 1975 and 2005. They found a structural break in the relationship between economic growth and external debt, where the external debt relief made more resources available for economic growth.…”
Section: Empirical Literaturementioning
confidence: 99%
“…A study by Ekperiware and Oladeji (2012) examined the effect of external debt relief on economic growth in Nigeria using regression technique on quarterly time series of external debt, external debt service and real gross domestic product. Applying Chowtest to the regression result they found that there was a structural break in the relationship between economic growth and external debt in Nigeria during the period 1975 to 2005.…”
Section: Copyright © International Association Of Africanmentioning
confidence: 99%
“…Ekperiware and Oladeji, [16] examined the structural break relationship between budget deficit and economic performance in Nigeria. The study employed a quarterly time series data of budget deficit, budget deficit service and real GDP from 1980-2009.…”
Section: Empirical Reviewmentioning
confidence: 99%